2006
DOI: 10.1111/j.1540-8191.2006.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Cardioversion Shortens Periods of Postoperative Atrial Fibrillation: Results of a Prospective, Multicenter Trial

Abstract: Internal cardioversion using Syncrus heart wires demonstrated effectiveness in treating postoperative AF. Especially, length of AF periods could be diminished by the system with the expectation of reduction in hospital length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 19 ], and also in a study by Dzemali et al . [ 18 ], using the so-called Syncrus wires, a similar version of the TADpole wires. The authors concluded that this treatment is expected to reduce hospital length of stay and therefore hospital costs, and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 19 ], and also in a study by Dzemali et al . [ 18 ], using the so-called Syncrus wires, a similar version of the TADpole wires. The authors concluded that this treatment is expected to reduce hospital length of stay and therefore hospital costs, and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the anode (zigzag) must still be placed carefully. The concept of bi-atrial cardioversion is already proven with good results and can be performed without anesthesia or only a little sedation [ 13 , 15 , 18 ]. Liebold treated 20 patients for atrial fibrillation (AF) with a shock energy up to 10 J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation